Determination of the Fracture Point for Inconel-718 Using Luder’s Band Method - Arupratan Gupta; Raghavendra C. Kamath (Engineering Proceedings)
The current scenario demands the usage of alternate materials with lower stress and stress–strain energy deformation for applications in gas turbines, chassis of automobiles, and biomedical instruments. The work on Inconel-718 can be carried out as it is a new material; it can be used for many applications in addition to its usage in automobiles. Inconel-718 is a superalloy of nickel (Ni) and chromium (Cr). Inconel-718 is corrosion resistant and oxidation resistant when subjected to extreme temperature conditions. But when applying tensile and compressive load, it bends, causing the formation of Luder’s band. The work analyses the formation of Luder’s band in Inconel-718. The methodology for detecting Luder’s band is based on the material structure. It also depends on the material’s rigidity modulus and the shear stress ratio to shear strain. The stress, harmonic, and thermal analyses were carried out using ANSYS to find the red-hot zone for the formation of Luder’s band. The results demonstrate that Luder’s band is mainly formed at the middle point of the frame. The stress for Inconel-718 is in the range of 0.064454 MPa to 81.514 MPa, whereas the frequency varies from 0.71157 to 475.87 Hz under vibration load. Conversely, while heating Inconel-718, the temperature varies from 1.6009 × 105 to 112.83 °C. The analysis shows that Inconel-718 is a better material for designing automobile parts.